Digital skills and work readiness: unveiling the mediating effect of digital self-efficacy - Suhada, Suhada; Idries, Fahmy Akbar; Wulandari, Novi Diah; Oktariantara, Ibra; Romandhani, Adinda Octa; Riyadho, Ananda (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
This study examines the effect of Digital Skills (DS) on Digital Work Readiness (DWR) among youth, emphasizing the mediating role of Digital Self-Efficacy (DSE). It highlights the importance of linking technical competence with psychological empowerment to prepare young jobseekers for a rapidly digitalized labour market. In Yogyakarta, Indonesia, 185 respondents between the ages of 18 and 35 participated in a quantitative survey. PLS-SEM was used to analyze the data and test the suggested correlations. The findings show that whereas DS has no direct effect on DWR, it considerably raises DSE. Rather, DSE completely mediates the association between DS and DWR, implying that to improve employability, digital competencies must be paired with confidence in utilizing technology.